Ultraviolet Radiation Biological and Medical Implications - Al-Sadek, Tarek; Yusuf, Nabiha (Current Issues in Molecular Biology, 2024)
Ultraviolet (UV) radiation plays a crucial role in the development of melanoma and non-melanoma skin cancers. The types of UV radiation are differentiated by wavelength: UVA (315 to 400 nm), UVB (280 to 320 nm), and UVC (100 to 280 nm). UV radiation can cause direct DNA damage in the forms of cyclobutane pyrimidine dimers (CPDs) and 6-4 photoproducts (6-4PPs). In addition, UV radiation can also cause DNA damage indirectly through photosensitization reactions caused by reactive oxygen species (ROS), which manifest as 8-hydroxy-2′-deoxyguanine (8-OHdG). Both direct and indirect DNA damage can lead to mutations in genes that promote the development of skin cancers. The development of melanoma is largely influenced by the signaling of the melanocortin one receptor (MC1R), which plays an essential role in the synthesis of melanin in the skin. UV-induced mutations in the BRAF and NRAS genes are also significant risk factors in melanoma development. UV radiation plays a significant role in basal cell carcinoma (BCC) development by causing mutations in the Hedgehog (Hh) pathway, which dysregulates cell proliferation and survival. UV radiation can also induce the development of squamous cell carcinoma via mutations in the TP53 gene and upregulation of MMPs in the stroma layer of the skin.